Re-reconsidering the role of temporal order in spoken word recognition. Issue 11 (November 2019) - Gregg, Julie; Inhoff, Albrecht W; Connine, Cynthia M
Spoken word recognition models incorporate the temporal unfolding of word information by assuming that positional match constrains lexical activation. Recent findings challenge the linearity constraint. In the visual world paradigm, Toscano, Anderson, and McMurray observed that listeners preferentially viewed a picture of a target word's anadrome competitor (e.g., competitor bus for target sub ) compared with phonologically unrelated distractors (e.g., well ) or competitors sharing an overlapping vowel (e.g., sun ). Toscano et al. concluded that spoken word recognition relies on coarse grain spectral similarity for mapping spoken input to a lexical representation. Our experiments aimed to replicate the anadrome effect and to test the coarse grain similarity account using competitors without vowel position overlap (e.g., competitor leaf for target flea ). The results confirmed the original effect: anadrome competitor fixation curves diverged from unrelated distractors approximately 275 ms after the onset of the target word. In contrast, the no vowel position overlap competitor did not show an increase in fixations compared with the unrelated distractors. The contrasting results for the anadrome and no vowel position overlap items are discussed in terms of theoretical implications of sequential match versus coarse grain similarity accounts of spoken word recognition. We also discuss design issues (repetition of stimulus materials and display parameters) concerning the use of the visual world paradigm in making inferences about online spoken word recognition.